2011
DOI: 10.1016/j.sysconle.2010.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Equivalence of rational representations of behaviors

Abstract: This article deals with the equivalence of representations of behaviors of linear differential systems. In general, the behavior of a given linear differential system has many different representations. In this paper we restrict ourselves to kernel and image representations. Two kernel representations are called equivalent if they represent one and the same behavior. For kernel representations defined by polynomial matrices, necessary and sufficient conditions for equivalence are well known. In this paper, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Remark 4.6. Theorem 4.3 substantially differs from the equivalence results in Gottimukkala, Fiaz, and Trentelman (2011), Trentelman (2010) and Yamamoto (2007, 2008) where C ∞ behaviors are defined as kernels of rational differential operators P. In Gottimukkala et al (2011), it is shown that the controllable parts of the C ∞ kernels of rational operators P and Q coincide if and only if there exists a unitary matrix U ∈ UL ∞, * such that P = UQ .…”
Section: Theorem 43 (Inclusion and Equivalence) Let Two Systems In Thementioning
confidence: 78%
“…Remark 4.6. Theorem 4.3 substantially differs from the equivalence results in Gottimukkala, Fiaz, and Trentelman (2011), Trentelman (2010) and Yamamoto (2007, 2008) where C ∞ behaviors are defined as kernels of rational differential operators P. In Gottimukkala et al (2011), it is shown that the controllable parts of the C ∞ kernels of rational operators P and Q coincide if and only if there exists a unitary matrix U ∈ UL ∞, * such that P = UQ .…”
Section: Theorem 43 (Inclusion and Equivalence) Let Two Systems In Thementioning
confidence: 78%
“…Proof of theorem Let G=M1N11,trueG~=P11Q1 and trueK~=P21Q2 be coprime factorizations over double-struckR[ξ]. Then, we have P=ker3.0235ptQ1()normaldnormaldt=im3.0235ptM1()normaldnormaldt (using Lemma 7.2 in ) and C=ker3.0235ptQ2()normaldnormaldt. Immediately, we then have PC=ker3.0235pt[]Q1ddtQ2ddt=M1()normaldnormaldtker3.0235pt(Q2M1)()normaldnormaldt.…”
Section: Robust Stabilizationmentioning
confidence: 96%
“…Representations of frakturB as in are called rational image representations . For more details on rational image representations, we refer the reader to .…”
Section: Linear Differential Systems and Their Representationsmentioning
confidence: 99%
“…For a given rational matrix R, we call a representation of B as R( d dt )w = 0 a rational kernel representation of B and write B = kerR( d dt ). For additional material on rational representations we refer to [6] and [7]. In this paper we will often assume that the rational matrices R(s) used in kernel representations have full row rank over the field of real rational functions.…”
Section: Polynomial and Rational Kernel Representationsmentioning
confidence: 99%
“…In this paper we will often assume that the rational matrices R(s) used in kernel representations have full row rank over the field of real rational functions. This is equivalent to saying that the kernel representation is minimal, see [5] and [6].…”
Section: Polynomial and Rational Kernel Representationsmentioning
confidence: 99%